Synthesis of Cyanoacetyl Oxazolidinones - Weeber, Kaitlyn M.; Schwarz, Jacob B. (Synthesis, 2012)
Carefully controlled displacement of chiral chloroacetyl imides with cyanide afforded previously unreported cyanoacetimides in good overall yield. Knoevenagel condensation of the cyanoacetimides to furnish acrylonitriles was also demonstrated.
Keywords: oxazolidinone; Knoevenagel; cyanoacetic; chloroacetic; tetrabutylammonium cyanide